Tips for academics a collection of short stories and personal opinion - Shamshuddin Jusop (Penerbit Universiti Putra Malaysia, 2014)
Unlike in the west or Japan, writers in Malaysia are unable to make a decent living via their creative skills. This is because not many people in the country like to read books/novels, let alone writing them. This is not consistent with the vision of Malaysia to be a developed country comes the year 2020. The idea of writing this memoir came from the fact that academics need to be convinced that writing is good in itself, and that books and papers in journals are good for the development of the nation. This memoir contains personal thoughts and short stories written based on the academic journey gone through by the author. It is hope that the information contained in the memoir would serve as tips for the young and up and coming academics.